Sotetsuflavone Induces Autophagy in Non-Small Cell Lung Cancer Through Blocking PI3K/Akt/mTOR Signaling Pathway in Vivo and in Vitro - Wang, Shaohui; Xu, Xiaoling; Hu, Yanlan; Lei, Tao; Liu, Tongxiang (Frontiers in Pharmacology, 2019)
Non-small cell lung cancer (NSCLC) is a globally scaled disease with a high incidence and high associated mortality rate. Autophagy is one of the important physiological activities that helps to control cell survival, influences the dynamics of cell death, and which plays a crucial role in the pathophysiology of NSCLC. Sotetsuflavone is a naturally derived and occurring flavonoid, and previous studies have demonstrated that sotetsuflavone possesses potential anti-cancer activities. However, whether or not sotetsuflavone induces autophagy，as well as has effects and influences cell death in NSCLC cells remains unclear. Thus in our study, we examined and elucidated the roles and underlying mechanisms of sotetsuflavone upon the dynamics of autophagy in NSCLC in vivo and in vitro. The results indicated that sotetsuflavone was able to inhibit proliferation, migration, and invasion of NSCLC cells. Mechanistically, sotetsuflavone was able to induce apoptosis by increasing the levels of expression of cytochrome C, cleaved-caspase 3, cleaved-caspase 9, and Bax, and contrastingly decreased levels of expression of Bcl-2. In addition, we also found that decreased levels of expression of Cyclin D1 and CDK4 caused arrest of the G0/G1 phases of the cell cycle. Furthermore, we also found that sotetsuflavone could induce autophagy which in turn can play a cytoprotective effect on apoptosis in NSCLC. Sotetsuflavone induced autophagy appeared related to the blocking of the PI3K/Akt/mTOR pathway. Our in vivo study demonstrated that sotetsuflavone significantly inhibited the growth of xenograft model inoculated A549 tumor with high a degree of safety. Taken together these findings suggest that sotetsuflavone induces autophagy in NSCLC cells through its effects upon blocking of the PI3K/Akt/mTOR signaling pathways. Our study may provide a theoretical basis for future clinical applications of sotetsuflavone and its use as a chemotherapeutic agent for treatment of NSCLC.